ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEANDALAN DAN KETEPATAN LAPORAN KEUANGAN SATUAN KERJA PERANGKAT DAERAH PADA PEMERINTAH KABUPATEN MINAHASA TENGGARA - Kosegeran, Anando Iphan; Kalangi, Lintje; Wokas, Heince (ACCOUNTABILITY, 2016)
This research is motivated by the fact that the financial statements of local government in Fiscal Year 2008 through Fiscal Year 2012, getting Disclaimer opinion of the Audit Board of the Republic of Indonesia Representatives of the Province of North Sulawesi. Therefore, with stronger demand and transparency of public institutions, both the center and in the regions, the researchers are interested in examining the "analysis of the factors affecting the reliability and accuracy of financial statements on education in Southeast Minahasa regency government. This study aims to determine whether the factors of human resource capacity, utilization of information technology and internal control of accounting affect the reliability and accuracy of financial reports on education in Southeast Minahasa Government. This study uses a quantitative research that emphasizes the hypothesis testing. The analytical method used in this research is multiple linear regression analysis, whereas for the processing of research data using SPSS version 21. The test results partially variable by using the criteria of significance <0.1 indicates that, human resource capacity, utilization of information technology and internal accounting pegendalian significant effect on the reliability and accuracy of the financial statements of the local work force in Southeast Minahasa regency government. While the test together shows that the human resource capacity, utilization of information technology and accounting internal control significant effect on the reliability and accuracy of the financial statements of the local work force in Southeast Minahasa regency government. Keywords: Capacity of Human Resources, Information Technology, Internal Control, Reliability and Accuracy of Government Financial Statements, SKPD.